The influence of low-concentration γ-Fe2O3 magnetic nanoparticles in a poly(ether-b-ester) copolymer matrix on interfacial polarization and glass transition - Majszczyk, J.; Guskos, N.; Typek, J.; V. Likodimos; Maryniak, M.; Roslaniec, Z.; Kwiatkowska, M.; Petridis, D. (Journal of Non-Crystalline Solids, 2006)
A new poly(ester-b-ether) copolymer filled with magnetic γ-Fe2O3 nanoparticles of low concentration (0.1 and 0.3 wt%) has been synthesized, with poly(ethylene terephthalate) (PET) as a rigid segment and poly(tetraoxymethylene) (PTMO) as the flexible segment at the ratio of 50 wt%. The filler was used in the form of suspension or solid powder. The dielectric spectroscopy results for these materials, in a wide range of frequencies and temperatures, are presented and compared with similar results for a pure polymeric matrix. Two relaxation processes, α and β, have been observed clearly in all samples at about 253 K and 163 K, respectively. The α process was shifted towards the lower temperatures as the nanoparticle content increased, while the β-relaxation was unaffected by the doping. The interfacial polarization effect was observed in the samples with nanoparticles, less pronounced for the larger nanoparticles. © 2006 Elsevier B.V. All rights reserved.
cited By 16